PENERAPAN ALGORITMA APRIORI UNTUK MENCARI POLA PENJUALAN PRODUK DANA PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK KANCA JAKARTA PASAR MINGGU - Sutrisno Sutrisno (Jurnal Sistem Informasi dan Informatika (Simika), 2020)
Various funding products which are offered by a bank sometimes make the clients tend to change their choices into other products from different banks. We need to make specific strategy so that we can dominate the market of this funding product. There will be selling reduction in this product if the used strategy is not appropriate. A company can use Data Mining process in order to reach the maximum profit of the fund’s selling products. One of the processes is by using priory algorithm. The association rules can be found by using this priory algorithm. Then, the rules can be used as a fund selling pattern towards the clients. The purpose of priory algorithm is to find the frequent item sets that are run in a group of data. Priory analysis defined as a process of finding all the priory rules which is qualified to support and to confidence.